Light microscopy proved to be useful technique for morpho‐anatomical examination of four wild plant species growing sideways wastewater tunnels. Issue 11 (7th May 2021) - Nadeem‐Ullah,; Ashraf, Waqas; Shafiq‐ur‐Rehman,; Jaffer, Mehwish; Qurat‐ul‐ain,
Abstract: The present study was conducted to determine the influence of wastewater used for irrigation purposes on anatomical characters of four wild plants with the help of light microscopy (LM). The plant selected were Trianthema portulacastrum L., Amaranthes viridis L., Portulaca oleracea L., and Persicaria barbata L. This wastewater comprises of municipal, industrial, and dairy waste containing organic matter, Ca ++, Mg ++, nitrogen, phosphorus, and potassium. It was found that T. portulacastrum L. and P. oleracea L. were directly affected and the size of vascular tissues and cortex reduced many times as compared to control, while on the other hand A. viridis L. and Persicaria berbata L. showed high growth than control these characters were clear using LM technique. Abstract : The research was planned to investigate the effect of irrigated waste water on plant anatomy. Light microscopy proved to be helpful tool in identification of anatomical character.